Association of obesity with disease outcome in multiple sclerosis. Issue 1 (1st November 2022) - Lutfullin, Isabel; Eveslage, Maria; Bittner, Stefan; Antony, Gisela; Flaskamp, Martina; Luessi, Felix; Salmen, Anke; Gisevius, Barbara; Klotz, Luisa; Korsukewitz, Catharina; Berthele, Achim; Groppa, Sergiu; et al.
Abstract : Background: Obesity reportedly increases the risk for developing multiple sclerosis (MS), but little is known about its association with disability accumulation. Methods: This nationwide longitudinal cohort study included 1066 individuals with newly diagnosed MS from the German National MS cohort. Expanded Disability Status Scale (EDSS) scores, relapse rates, MRI findings and choice of immunotherapy were compared at baseline and at years 2, 4 and 6 between obese (body mass index, BMI ≥30 kg/m 2 ) and non-obese (BMI <30 kg/m 2 ) patients and correlated with individual BMI values. Results: Presence of obesity at disease onset was associated with higher disability at baseline and at 2, 4 and 6 years of follow-up (p<0.001). Median time to reach EDSS 3 was 0.99 years for patients with BMI ≥30 kg/m 2  and 1.46 years for non-obese patients. Risk to reach EDSS 3 over 6 years was significantly increased in patients with BMI ≥30 kg/m 2 compared with patients with BMI <30 kg/m 2 after adjustment for sex, age, smoking (HR 1.87; 95% CI 1.3 to 2.6; log-rank test p<0.001) and independent of disease-modifying therapies. Obesity was not significantly associated with higher relapse rates, increased number of contrast-enhancing MRI lesions or higher MRI T2 lesion burden over 6 years of follow-up. Conclusions: Obesity in newly diagnosed patients with MS is associated with higher disease severity and poorer outcome. Obesity management could improve clinical outcome of MS.